Feel better, no matter what : a 4-week course to love the life you have right now - James, Michael (Watkins, 2021)
A 4-week course offering new tools to deal with the challenging emotions that get in the way of enjoying life. These incredible self-soothing methods, created by a highly respected life coach and inspirational speaker, really do work. Do you feel your life could be a lot more successful and fun - but it's not happening? Do your overthinking and intense emotions keep getting in the way of enjoying life? Do you struggle following advice such as "let it go", "be positive" and "live in the moment"? Do you keep falling back - despite your best efforts - into the same old relationship problems, mood swings and self-esteem issues? This book has a radical message: You don't need self-improvement to enjoy your life. You don't need to be better. You are ok just as you are. Step-by-step, this innovative 4-week course teaches you to free yourself from intrusive thoughts and challenging emotions, so you can step out bravely into the world, not caring so much what others think. There are no complicated theories, rituals or practices here, only simple techniques that will enable you to step away from overthinking, self-criticism and fear to live as your already empowered Real Self. Living a good life doesn't need to be complicated. Amazing things happen when you know how to be yourself and love yourself, shining bright as who you are.